Answer:
(a) ![f'(x)=-\frac{2}{x^3}](https://tex.z-dn.net/?f=f%27%28x%29%3D-%5Cfrac%7B2%7D%7Bx%5E3%7D)
(b) ![y=-0.25x+0.75](https://tex.z-dn.net/?f=y%3D-0.25x%2B0.75)
Step-by-step explanation:
The given function is
.... (1)
According to the first principle of the derivative,
![f'(x)=lim_{h\rightarrow 0}\frac{f(x+h)-f(x)}{h}](https://tex.z-dn.net/?f=f%27%28x%29%3Dlim_%7Bh%5Crightarrow%200%7D%5Cfrac%7Bf%28x%2Bh%29-f%28x%29%7D%7Bh%7D)
![f'(x)=lim_{h\rightarrow 0}\frac{\frac{1}{(x+h)^2}-\frac{1}{x^2}}{h}](https://tex.z-dn.net/?f=f%27%28x%29%3Dlim_%7Bh%5Crightarrow%200%7D%5Cfrac%7B%5Cfrac%7B1%7D%7B%28x%2Bh%29%5E2%7D-%5Cfrac%7B1%7D%7Bx%5E2%7D%7D%7Bh%7D)
![f'(x)=lim_{h\rightarrow 0}\frac{\frac{x^2-(x+h)^2}{x^2(x+h)^2}}{h}](https://tex.z-dn.net/?f=f%27%28x%29%3Dlim_%7Bh%5Crightarrow%200%7D%5Cfrac%7B%5Cfrac%7Bx%5E2-%28x%2Bh%29%5E2%7D%7Bx%5E2%28x%2Bh%29%5E2%7D%7D%7Bh%7D)
![f'(x)=lim_{h\rightarrow 0}\frac{x^2-x^2-2xh-h^2}{hx^2(x+h)^2}](https://tex.z-dn.net/?f=f%27%28x%29%3Dlim_%7Bh%5Crightarrow%200%7D%5Cfrac%7Bx%5E2-x%5E2-2xh-h%5E2%7D%7Bhx%5E2%28x%2Bh%29%5E2%7D)
![f'(x)=lim_{h\rightarrow 0}\frac{-2xh-h^2}{hx^2(x+h)^2}](https://tex.z-dn.net/?f=f%27%28x%29%3Dlim_%7Bh%5Crightarrow%200%7D%5Cfrac%7B-2xh-h%5E2%7D%7Bhx%5E2%28x%2Bh%29%5E2%7D)
![f'(x)=lim_{h\rightarrow 0}\frac{-h(2x+h)}{hx^2(x+h)^2}](https://tex.z-dn.net/?f=f%27%28x%29%3Dlim_%7Bh%5Crightarrow%200%7D%5Cfrac%7B-h%282x%2Bh%29%7D%7Bhx%5E2%28x%2Bh%29%5E2%7D)
Cancel out common factors.
![f'(x)=lim_{h\rightarrow 0}\frac{-(2x+h)}{x^2(x+h)^2}](https://tex.z-dn.net/?f=f%27%28x%29%3Dlim_%7Bh%5Crightarrow%200%7D%5Cfrac%7B-%282x%2Bh%29%7D%7Bx%5E2%28x%2Bh%29%5E2%7D)
By applying limit, we get
![f'(x)=\frac{-(2x+0)}{x^2(x+0)^2}](https://tex.z-dn.net/?f=f%27%28x%29%3D%5Cfrac%7B-%282x%2B0%29%7D%7Bx%5E2%28x%2B0%29%5E2%7D)
![f'(x)=\frac{-2x)}{x^4}](https://tex.z-dn.net/?f=f%27%28x%29%3D%5Cfrac%7B-2x%29%7D%7Bx%5E4%7D)
.... (2)
Therefore
.
(b)
Put x=2, to find the y-coordinate of point of tangency.
![f(x)=\frac{1}{2^2}=\frac{1}{4}=0.25](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7B1%7D%7B2%5E2%7D%3D%5Cfrac%7B1%7D%7B4%7D%3D0.25)
The coordinates of point of tangency are (2,0.25).
The slope of tangent at x=2 is
![m=(\frac{dy}{dx})_{x=2}=f'(x)_{x=2}](https://tex.z-dn.net/?f=m%3D%28%5Cfrac%7Bdy%7D%7Bdx%7D%29_%7Bx%3D2%7D%3Df%27%28x%29_%7Bx%3D2%7D)
Substitute x=2 in equation 2.
![f'(2)=\frac{-2}{(2)^3}=\frac{-2}{8}=\frac{-1}{4}=-0.25](https://tex.z-dn.net/?f=f%27%282%29%3D%5Cfrac%7B-2%7D%7B%282%29%5E3%7D%3D%5Cfrac%7B-2%7D%7B8%7D%3D%5Cfrac%7B-1%7D%7B4%7D%3D-0.25)
The slope of the tangent line at x=2 is -0.25.
The slope of tangent is -0.25 and the tangent passes through the point (2,0.25).
Using point slope form the equation of tangent is
![y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3Dm%28x-x_1%29)
![y-0.25=-0.25(x-2)](https://tex.z-dn.net/?f=y-0.25%3D-0.25%28x-2%29)
![y-0.25=-0.25x+0.5](https://tex.z-dn.net/?f=y-0.25%3D-0.25x%2B0.5)
![y=-0.25x+0.5+0.25](https://tex.z-dn.net/?f=y%3D-0.25x%2B0.5%2B0.25)
![y=-0.25x+0.75](https://tex.z-dn.net/?f=y%3D-0.25x%2B0.75)
Therefore the equation of the tangent line at x=2 is y=-0.25x+0.75.